Factors affecting pre-service teachers to adopt augmented reality in science learning - Rizki, Iqbal Ainur; Suprapto, Nadi; Awwalina, Denissa Putri; Wanti, Wilujeng Trismaya; Sabrina, Nadya Mazayu Nur (International Journal of Evaluation and Research in Education (IJERE), 2025)
The advancement of augmented reality (AR) technology and its application in education presents an opportunity for pre-service teachers to incorporate it into the learning process, particularly in science subjects with abstract and microscopic materials. However, the adoption of AR technology among pre-service teachers remains suboptimal. Therefore, this study aims to analyze the factors influencing pre-service teachers’ adoption of AR in science learning. By employing partial least squares structural equation modeling, we gathered 211 responses through a questionnaire. The developed model has met the criteria of validity and reliability. The study’s findings reveal that perceived control and learning content significantly influence behavioral intention, while visual attraction and knowledge-ability do not. Clearly, their focus is on pedagogically implementing AR technology rather than visually developing it. Thus, it is recommended to provide training for pre-service teachers to apply AR science because many of them need an understanding of integrating this technology as a science learning media. This research implies offering insightful analysis and practical suggestions for the successful integration of AR technology into science learning, especially by addressing the variables affecting its uptake.